Evolução dos cursos de computação do Instituto Federal do Amapá campus Macapá com base em avaliações oficiais - BRITO NETO, Olavo Nylander (Instituto Federal do Amapá, 2021)
The undergraduate courses in its creation go through the process of opening, with authorization, recognition of course and Enade with the Ministry of Education. Know the steps and know how to organize becomes crucial during this process and few reports are recorded from the expertises of the Institutions of undergraduate courses in the country. This paper aims to present the results of official evaluations and concomitant applied in undergraduate courses of Federal Institute of Education, Science and Technology of Amapá (IFAP), aiming to show the stages, difficulties and challenges during these obligatory phases for the Higher Education courses in Brazil and to show the evolution of the computer courses of IFAP in their initial years of consolidation in the state of Amapá. This work is organized describing the profile of the institution, the evaluation structure and implementation monitoring, reporting the evaluations, results and considerations, detailing its results based on the dimensions: didactic-pedagogical organization, teacher team and tutorial and infrastructures directly related to the courses involved.